MOLECULAR STUDIES OF AROMATIC AND NON AROMATIC RICE (ORYZA SATIVA L.) GENOTYPES FOR QUALITY TRAITS USING MICROSATELLITE MARKERS - VHORA, ZAINAB; TRIVEDI, RUCHI; CHAKRABORTY, SUDESHNA; RAVIKIRAN , RALLAPALLI; N. SASIDHARAN (The Bioscan, 2013)
The present study was performed to analyze the genetic diversity among aromatic and non-aromatic rice genotypes using microsatellite markers (SSR). For the investigation, 20 rice cultivars of aromatic, non-aromatic, and quality traits were studied using 25 Rice Microsatellite (RM) markers, among which 15 markers were used for analyzing aromatic and nonaromatic rice genotypes. These markers generated higher level of polymorphism due to which they generated 356 polymorphic reproducible bands with 164 loci. The remaining ten markers are used for the study of quality traits which shown 222 polymorphic bands with 101 alleles. The cluster analysis using SSR markers could distinguish the different genotypes. The dendogram generated on the principle of Unweighted Pair Wise Method using Arithemetic Average (UPGMA) was constructed by Jaccard’s Coefficient and the genotypes were grouped in to clusters. The dendogram developed for aroma and quality traits showed that the genotypes with common phylogeny and geographical orientation tend to cluster together.